Early Deafness Increases the Face Inversion Effect But Does Not Modulate the Composite Face Effect - de Heering, Adélaïde; Rossion, Bruno; Pascalis, Olivier (Frontiers in Psychology, 2012)
Early deprivation in audition can have striking effects on the development of visual processing. Here we investigated whether early deafness induces changes in holistic/configural face processing. To this end, we compared the results of a group of early deaf participants to those of a group of hearing participants in an inversion-matching task (Experiment 1) and a composite face task (Experiment 2). We hypothesized that deaf individuals would show an enhanced inversion effect and/or an increased composite face effect compared to hearing controls in case of enhanced holistic/configural face processing. Conversely, these effects would be reduced if they rely more on facial features than hearing controls. As a result, we found that deaf individuals showed an increased inversion effect for faces, but not for non-face objects. They were also significantly slower than hearing controls to match inverted faces. However, the two populations did not differ regarding the overall size of their composite face effect. Altogether these results suggest that early deafness does not enhance or reduce the amount of holistic/configural processing devoted to faces but may increase the dependency on this mode of processing.